The Study of Social Deixis Used in the Film "Avengers" - Jundi Mukhtaruddin; Fadhil, Muhammad; Widyamurti, Arif Rahman; Wibisono, Abian Bagus; Firdaus, Wahyu Muhammad; Laila, Malikatul (Candradimuka: Journal of Education, 2024)
This study investigates the role of social deixis in the film "Avengers" and its influence on character interactions, narrative development, and audience engagement. Social deixis, a linguistic phenomenon involving the use of language to establish social relationships and navigate social contexts, plays a vital role in shaping the dynamics of communication within the Avengers team. By closely examining the dialogue and language choices of the characters, this study aims to identify the types of deixis employed and explore their implications for character development and plot progression. Through a qualitative analysis of selected scenes, the findings reveal the diverse range of social deixis strategies utilized, including personal deixis, honorific deixis, politeness deixis, demonstrative deixis, and more. These linguistic choices contribute to the establishment of power dynamics, the formation of group identity, and the conveyance of emotional and interpersonal nuances. Moreover, they enhance the audience's understanding of the characters' relationships, motivations, and conflicts. This study enhances our understanding of the intricate interplay between language, social interaction, and narrative construction in the context of a popular film franchise. It provides valuable insights into the significance of social deixis in cinematic storytelling and opens avenues for further research in the field of discourse analysis, linguistics, and film studies.